Hybrid chitosan/amniotic membrane-based hydrogels for articular cartilage tissue engineering application. Issue 15 (12th October 2020) - Toniato, Tatiane Venturott; Stocco, Thiago Domingues; Martins, Danilo dos Santos; Santanna, Luciana Barros; Tim, Carla Roberta; Marciano, Fernanda Roberta; Silva-Filho, Edson Cavalcanti; Campana-Filho, Sérgio Paulo; Lobo, Anderson de Oliveira
Abstract: A hybrid hydrogel combining collagen and chitosan (Ch) and human amniotic membranes (AM) were produced. To produce hybrid hydrogels, a fixed concentration of chitosan (2%) was used, adding AM as a booster at the concentrations of 2.5, 5.0. and 10.0% ( w/w ). DSC curves showed the denaturation of collagen. The swelling capacity of hydrogels ranged between 333 ± 19% and 368 ± 28%. The groups Ch-1.0 mg/mL and Ch-2.0 mg/mL had an elastic modulus 27% higher than the other groups. Graphical Abstract: